2012
DOI: 10.2134/agronj2011.0387
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Use by Yam as Affected by Mineral Fertilizer Application

Abstract: Soil fertility decline and high N demand during plant growth are cited as main causes of low yield in yam (Dioscorea spp.). As information regarding fertilizer N use in yam is lacking, a field experiment was undertaken in 2006 and repeated in 2007 in central Côte d'Ivoire using 15N (15NH415NO3) labeled fertilizers to monitor N uptake and fertilizer use efficiency in D. alata. The 15N‐labeled fertilizer was added in two splits (at 90 and 130 d after planting) for a target tuber yield of 40 Mg fresh tuber ha−1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 36 publications
0
18
0
2
Order By: Relevance
“…Equating N s to U 0 assumes that no interactions occur to increase or decrease N s when the plants are fertilized. However, there is evidence that N fertilization may affect the N cycle in ways that cause N s to differ from U 0 , indicating that N fertilization can stimulate N mineralization from organic matter (the priming effect) and reduce the quantity and rate of N immobilization by crop residues (Broadbent, 1965;Jenkinson et al, 1985;Green and Blackmer, 1995;Hgaza et al, 2012). Future recommendation systems might need to take these interactions into account.…”
Section: Fundamental Background Information About Nitrogenmentioning
confidence: 99%
“…Equating N s to U 0 assumes that no interactions occur to increase or decrease N s when the plants are fertilized. However, there is evidence that N fertilization may affect the N cycle in ways that cause N s to differ from U 0 , indicating that N fertilization can stimulate N mineralization from organic matter (the priming effect) and reduce the quantity and rate of N immobilization by crop residues (Broadbent, 1965;Jenkinson et al, 1985;Green and Blackmer, 1995;Hgaza et al, 2012). Future recommendation systems might need to take these interactions into account.…”
Section: Fundamental Background Information About Nitrogenmentioning
confidence: 99%
“…Whether such an effect would also occur following organic fertilizer inputs should be assessed. In the same study, Hgaza et al ( 2012 ) observed a maximum N fertilizer recovery of below 30% in the tuber. This limited recovery was explained by the low planting density (one plant m −2 ), which is typical for West Africa and by the coarse and superficial root system of D. alata (Hgaza et al, 2011 ).…”
Section: Importance Of Soil Fertility For Yam Productionmentioning
confidence: 70%
“…Melteras et al ( 2008 ) observed radial of roots of D. esculenta that were longer than 3 m and suggested that this would lead to wrong interpretation of fertilizer trial results as an unfertilized plant would be able to take up nutrients from a fertilized plot. On the contrary, no N transfer was observed from fertilized to unfertilized plots in a study conducted with 15 N labeled fertilizer on D. alata with 1 m space between plots (Hgaza et al, 2012 ). Except in the work done by Kassi et al ( 2017 ), no relation linking soil properties and yam tuber yield has been published.…”
Section: Importance Of Soil Fertility For Yam Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NUE values found for the whole plant were low but within the broad range of values reported in the literature. Relatively low NUE values have been reported for a great variety of cropping systems worldwide, e.g., 14-20% for a maize crop in China [20], 22-33% for maize intercropped with trees in the humid tropics [21], 23% for water yam in Ivory Coast [22]. Indeed, a comparison between these results and ours is difficult because of the many different pedoclimatic conditions and fertilizing practices (rate, timing, and placement) involved in each specific study.…”
Section: Fate Of Fertilizer N In Plantsmentioning
confidence: 99%